F‐wave parameters and body mass index in carpal tunnel syndrome - Adebayo, Philip B. (Brain Behav, 2021)
BACKGROUND: Severe carpal tunnel syndrome (CTS) readily lends itself to both clinical and electrophysiological recognition. The uncertainty sometimes is in identifying and quantifying motor involvement in mild and, perhaps, in moderate CTS. Our study aimed to evaluate F responses in mild and moderate CTS and determine the contribution of BMI to the F‐wave parameters. METHODS: A retrospective review of the clinical and electrophysiological data of patients with CTS seen at the clinical neurophysiology laboratory of Aga Khan Hospital, Dar es Salaam, between 1 August 2017 and 31 July 2019 was retrieved. Carpal tunnel syndrome was graded according to the electrophysiological criteria of Padua. The F‐wave parameters of patients with mild‐to‐moderate CTS were analyzed and compared with asymptomatic controls. RESULT: We studied 91 hands. Twenty‐two hands were asymptomatic controls, 30 hands had mild CTS, and 39 hands had moderate CTS. Patients with moderate CTS were more obese (p =.011), had more females (p =.044), and were older (p= <0.001). F‐wave parameters were not convincingly different between mild and moderate CTS. F‐wave chronodispersion (p =.035) and F‐wave persistence (0.019) were significantly different between nonobese control and mild and moderate CTS. Median–ulnar F‐wave latency difference (FWLD) was significant between obese patients with mild CTS and moderate CTS scores (p =.017). CONCLUSION: Although a clear difference exists between F‐wave parameters in asymptomatic controls and those with CTS, the F‐wave study is inadequate in distinguishing mild and moderate CTS even in the context of BMI. Median–ulnar F‐wave latency difference (FWLD) appeared to be a promising discriminant parameter between obese patients with mild CTS and those with moderate CTS.